Activin‐βC modulates cachexia by repressing the ubiquitin‐proteasome and autophagic degradation pathways. Issue 4 (23rd May 2015) - Marino, Francesco Elia; Risbridger, Gail; Gold, Elspeth
Abstract: Background: Cancer‐associated cachexia and muscle wasting are considered key determinants of cancer‐related death and reduction in the quality of life of cancer patients. A crucial link has been established between activin signaling and skeletal muscle atrophy‐hypertrophy. We previously showed that activin‐βC, a novel activin‐A antagonist, is a tumor modulator that abolishes the cancer‐associated cachexia in a mouse genetic model of gonadal tumorigenesis, in which the normal balance of inhibin/activin signalling is disrupted by a targeted mutation in the Inha gene (inhibin α‐KO mouse). This study aimed to identify the molecular mechanism by which activin‐βC increases survival and abolishes cancer‐associated cachexia in α‐KO mice. We hypothesized that overexpression of activin‐βC modulates the cachexia phenotype by antagonizing the activin signaling pathway and repressing muscle wasting via the ubiquitin‐proteasome and the autophagic‐lysosomal degradation pathways. Methods: Male and female ActC++, α‐KO, and α‐KO/ActC++ mice and WT littermate controls were studied. Western blot analysis for the specific E3 ubiquitin ligases, atrogin‐1 and MuRF1, markers of the autophagic‐lysosomal pathway, Beclin‐1, p62, and LC3A/B, effectors Smad‐2, Smad‐3 and myostatin was performed in the gastrocnemius of age‐matched mice. Histopathology of the gastrocnemius and survival analysis were also conducted in animals from the same breeding cohort. Serum levels of activin‐A, inflammatory cytokines, hormonal profile, and bone density were also assessed. Results: Increased levels of atrogin‐1, MuRF‐1, Beclin‐1, p62, LC3A/B‐I, Smad‐2 and serum levels of activin‐A were noted in the α‐KO mice. These mice developed gonadal cancers followed by severe weight loss, and reduced survival. Overexpression of activin‐ βC antagonized the activin signaling cascade, attenuating the ubiquitin‐proteasome and the autophagic‐lysosomal degradation pathways, and reduced serum levels of activin‐A. α‐KO/ActC++ mice displayed a less aggressive cachectic phenotype, reduced tumor weight, and prolonged survival. Conclusion: Our findings show for the first time a specific effect of activin‐βC on muscle wasting and transcription factors involved in muscle protein degradation. The study indicates that activin‐βC may be a novel therapy to abrogate cancer‐associated weight loss and prolong survival.